EVALUASI EFEKTIVITAS PROGRAM PELATIHAN DI BALAI LATIHAN KERJA KABUPATEN PASAMAN BARAT DALAM PERSPEKTIF MANAJEMEN KEPEMIMPINAN (PENDEKATAN KIRKPATRICK MODEL) - Nurul, Muhammad; Giatman, M.; Yuliarma, Yuliarma; Mardizal, Jonni (STKIP Pesisir Selatan, 2025)
Objective: This study aims to evaluate the effectiveness of training programs at Pasaman Barat Vocational Training Center (BLK) using the Kirkpatrick Model framework from a managerial leadership perspective. A qualitative descriptive approach was employed, supported by quantitative data from 129 participants trained in 2024 across four vocational fields: Electrical Engineering, Information and Communication Technology, and Automotive Engineering. Data show that 11,63% of trainees gained employment after training, and 54,26% obtained BNSP certification. The analysis applied the four levels of the Kirkpatrick Model Reaction, Learning, Behavior, and Result linked with the managerial and participatory leadership style of the BLK director. Findings reveal that program effectiveness remains suboptimal, particularly at the behavior and result levels related to job placement and industrial competence improvement. Managerial leadership plays a significant role in enhancing instructor motivation, cross-department collaboration, and quality assurance. The study recommends strengthening post-training monitoring, increasing collaboration with industries, and enhancing leadership capacity among BLK managers to sustain training effectiveness.